Effects of sintering temperature on morphology and dielectric properties of SrTio₃-doped CaCu₃Ti₄O₁₂ prepared via mechanical alloying - Abdullah, Mutia Suhaibah (2018)
Perovskite materials are well known for their ability to produce high dielectric constant which had led to many important industrial applications in microelectronics and memory devices. In this research, the relationship between morphology and dielectric properties of perovskite Strontium Titanate, ST and the perovskite-related material Calcium Copper Titanate, CCTO were studied. Most of the works done on CCTO-ST system basically cover the composition of CCTO-ST towards their electrical properties, effect of doping and their dielectric and microstructure relationship at higher sintering temperatures. However, not much work was done on tracking the evolution of CCTO-ST at low sintering temperature until they evolve to their final sintering temperature. Hence, in this thesis, research findings on the parallel evolution of such morphological properties and dielectric properties were reported and elucidate their relationship. CCTO, ST and CCTO doped with ST were prepared via mechanical alloying using High Energy Ball Milling in a hardened steel vial for 10, 12 and 2 hours respectively. The pellet samples were sintered from 500 °C to final temperature at 100 °C increment. The phase and crystal structure formation of the synthesized materials were confirmed by X-ray diffraction (XRD) while the evolution of microstructure properties was studied using Field Emission Scanning Electron Microscopy, FeSEM. The as-milled ceramic confirmed the existence of CCTO peak for the CCTO and CCTO-ST samples. After the sintering process, the highly crystalline phase of ST, CCTO and CCTO-ST was form at 1000 °C, 1000 °C and 800 °C respectively. FeSEM revealed an improvement in grain growth as the sintering increased where the grain size increased from 126.5 nm to 559.6 nm (ST), 82 nm to 18467 nm (CCTO) and from 114.54 nm to 1658.02 nm (CCTO-ST). The relative densities also show an increment where it reaches 73.59%, 98.92% and 22.26% for CCTO, ST and CCTO-ST respectively at their final sintering temperature. The dielectric studies were carried out by using Impedance Analyzer in the frequency range 40 Hz to 1 MHz and varies from 30 °C to 200 °C. For ST samples, the dielectric constant showed interfacial polarization at low frequency and ɛr’ value increases from 49.753 to 517.603 at 100 kHz as the sintering temperature arise. Meanwhile, tangent loss (tan δ) was found in the range of 0.069 to 0.02 at 100 kHz at room temperature. For CCTO, the permittivity studies showed two polarizations occur. The relaxation belonged to the interfacial polarization. At 100 kHz, the ɛr’ varies from 72 to 5573 for CCTO samples sintered at 500 oC to 1100 oC. The frequency dependence of loss tangent, tan δ decreased to almost zero at higher frequencies for all sintering temperatures. The influence of ST on CCTO system does improved the microstructure and reduced the dielectric properties. The dielectric constant for CCTO-ST nanocomposite is lower than in CCTO ceramics which in the range of 139.956 at 100 kHz. However ST as a dopant also reduced tan δ to 0.03. CCTO-ST sintered at 1000 °C showed a prominent candidate for energy storage devices as it has the lowest tangent loss and moderate ɛr’.